PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PT. DJARUM Tbk CABANG BATAM DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Arjulis A; Edwin Agung Wibowo; Oktavianti Oktavianti (EQUILIBIRIA, 2017)
The existence of human resource in the company has a very important role. Business domain nowadays forced to create high employee’s performance to company development. A company has to create and increase performance. In a way of increasing employee’s performance, company takes some ways such as giving a proper compensation, motivation, create a support working area, education, and training. Nowadays, business competition that became tighter make the company confronted with challenge to maintain viability.This research was held in PT. Djarum Tbk. This research use Compensation as Independent Variable, Motivastion as Intervening Variable, and Performance as Dependen Variable. The goal of this research is to analysis compensation’s influence to employee’s performance through motivation as intervening variable. Sample that used in this research are 57 PT. Djarum Tbk employees with using simple random sampling method. Analysis that used in this research are validity test, reliability test, classic assumption test, model test, regresion and intervening test. Those data that had been processed produce  regression equation below : Based on t-test and first linier regression above show us that compensation has a positive and significant influence to motivation and on the second linier regression show us that compansation and motivation has a positive and significant influence to performance. And based on those two linier regression’s above we can do ntervening test, so its show that motivation can be a intervening variable because of standardized coefficient’s calculation for indirect influence of compensation to performance through motivation is bigger than calculation for direct influence of compensation to performance.